User signal recovery based on channel matrix division - GUO Bin; BAI Xue-mei; F.Mohammed (Tongxin xuebao)
Multi-user MIMO-OFDM channel dispersion effects can be considered as a set of instantaneous mixtures from the viewpoint of frequency bin（FB）.Upon the arrival of a new user,the new interferences will be introduced,resulting in an expanding channel matrix structure.The expanded matrix contains known and unknown information,a blind separa-tion structure containing two parts which correspond the two types of information.To select a blind separation method,a proposed method uses the correlation between the signals to derive a new structure of the mixing matrix.Then the signals from different users at each FB are separated using the known channel information,thus the uncertainty of blind separa-tion is corrected.The validity of the proposed method is demonstrated by computer simulations.